2006
DOI: 10.1590/s1806-83242006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional stability of distances between posterior teeth in maxillary complete dentures

Abstract: ABSTRACT:The aim of this study was to assess the displacement of posterior teeth in maxillary complete dentures stored in water at 37°C. Twenty acrylic resin-based maxillary complete dentures were constructed with the anterior teeth arranged in normal overlap and the posterior teeth in Angle class I. Metallic pins were placed on the labial cusp of the fi rst premolars (PM), and on the mesiolabial cusp of the second molars (M). The fi nal acrylic resin pressing was made in a metallic fl ask with aid of the RS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
(31 reference statements)
1
13
0
4
Order By: Relevance
“…Several studies have indicated that any lack of dimensional accuracy in denture bases produced during processing procedures is probably a consequence of one or more factors 7 …”
Section: Technical Aspects Of Fabricationmentioning
confidence: 99%
“…Several studies have indicated that any lack of dimensional accuracy in denture bases produced during processing procedures is probably a consequence of one or more factors 7 …”
Section: Technical Aspects Of Fabricationmentioning
confidence: 99%
“…Laboratory silicone has been used as an investment material for processing prosthesis instead of the traditional type III stone with great efficacy 11 . This material makes the whole manufacturing process easier and cleaner and reduces further risk of distortions when deflasking 12 . However, it is not known whether this material is capable of preventing teeth movements during the prostheses processing.…”
Section: Introductionmentioning
confidence: 99%
“…Bu safhada polimerizasyon büzülmesi tamamlanmış olacağından meydana gelen büzülme termal kökenli olup rezinlerin bileşimine bağlıdır. Gerilimler ve bunun sonucunda meydana gelen distorsiyonları gidermek için çeşitli muflalama teknikleri ve rezin formülasyonları geliştiril-mektedir (3)(4)(5).…”
Section: Gđrđşunclassified